2019
DOI: 10.1093/humrep/dez051
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative live birth rates in low-prognosis women

Abstract: STUDY QUESTION Do cumulative live birth rates (CLBRs) over multiple IVF/ICSI cycles confirm the low prognosis in women stratified according to the POSEIDON criteria? SUMMARY ANSWER The CLBR of low-prognosis women is ~56% over 18 months of IVF/ICSI treatment and varies between the POSEIDON groups, which is primarily attributable to the impact of female age. WHAT IS KNOWN ALREADY The POSEIDON group recently proposed a new stratification for low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
48
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 48 publications
9
48
3
Order By: Relevance
“…Leijdekkers et al . reported that the conservative CLBR after 18 months reached 58% in patients younger than 35 years and 37% in those aged 35 years or older; the optimal CLBR reached 60% and 41% for the same age groups, respectively—all higher than those in our study.…”
Section: Discussioncontrasting
confidence: 62%
“…Leijdekkers et al . reported that the conservative CLBR after 18 months reached 58% in patients younger than 35 years and 37% in those aged 35 years or older; the optimal CLBR reached 60% and 41% for the same age groups, respectively—all higher than those in our study.…”
Section: Discussioncontrasting
confidence: 62%
“…According to the literature (18) and the data of our centre, live birth rates among women with DOR in the control arm were around 25.0%. Based on other studies within fertility care as well as the discussion by gynaecologist and epidemiologists, we assume that the minimal clinical important difference to make time-lapse system preferable over conventional incubator would be 10.0%.…”
Section: Sample Size Calculationmentioning
confidence: 88%
“…They have found about 56% CLBR in poor-prognosis ART/IVF patients over 18 months with variations between the various POSEIDON groups, primarily attributable to the effect of age. Young patients who were classified, according to the POSEDON stratification, as unexpected poor responders (group 1 reached a CLBR of about 65%, whereas the young expected poor responders (group 3) achieved only 59% CLBR (23). In comparison the older unexpected poor responders (group 2) achieved a CLBR of only 42%, and the older expected poor responders (group 4) only 39% (23).…”
Section: Definition and Etiologymentioning
confidence: 92%
“…It may, in addition, enable the fertility specialist to more accurately advise their patients regarding their treatment prognosis. Indeed, the first relevant indication and confirmation of the low prognosis of POR, stratified according to the POSEIDON criteria, has been recently published (23). In this Dutch multicenter study of 551 poor prognosis patients, cumulative live birth rates (CLBRs) over 18 months and several IVF/ICSI cycles was correlated to the POSEIDON groups (23).…”
Section: Definition and Etiologymentioning
confidence: 99%
See 1 more Smart Citation